Characterisation of PM10 emissions from woodstove combustion of common woods grown in Portugal - Gonçalves, Cátia; Alves, Célia; Evtyugina, Margarita; Mirante, Fátima; Pio, Casimiro; Caseiro, Alexandre; Schmidl, Christoph; Bauer, Heidi; Carvalho, Fernando (Atmospheric Environment, 2010)
A series of source tests was performed to evaluate the chemical composition of particle emissions from the woodstove combustion of four prevalent Portuguese species of woods: Pinus pinaster (maritime pine), Eucalyptus globulus (eucalyptus), Quercus suber (cork oak) and Acacia longifolia (golden wattle). Analyses included water-soluble ions, metals, radionuclides, organic and elemental carbon (OC and EC), humic-like substances (HULIS), cellulose and approximately l80 organic compounds. Particle (PM10) emission factors from eucalyptus and oak were higher than those from pine and acacia. The carbonaceous matter represented 44e63% of the particulate mass emitted during the combustion process, regardless of species burned. The major organic components of smoke particles, for all the wood species studied, with the exception of the golden wattle (0.07e1.9% w/w), were anhydrosugars (0.2e17% w/w). Conﬂicting with what was expected, only small amounts of cellulose were found in wood smoke. As for HULIS, average particle mass concentrations ranged from 1.5% to 3.0%. The golden wattle wood smoke presented much higher concentrations of ions and metal species than the emissions from the other wood types. The results of the analysis of radionuclides revealed that the 226 Ra was the naturally occurring radionuclide more enriched in PM10. The chromatographically resolved organics included n-alkanes, nalkenes, PAH, oxygenated PAH, n-alkanals, ketones, n-alkanols, terpenoids, triterpenoids, phenolic compounds, phytosterols, alcohols, n-alkanoic acids, n-di-acids, unsaturated acids and alkyl ester acids.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: Biomass burning; Emissions; GC-MS; Organic tracers; PM10; Woodstove